Using novel AFM lithography techniques to create flexible platforms for biomechanical measurements - Rizzo, Daniel Joseph (Tufts Archival Research Center, 2005)
Here we explore the validation of a novel technique that incorporates both the spatial and force resolution of the AFM with the temporal resolution of FRET. It has been shown that a technique known as nanografting can be used to immobilize proteins on gold substrates in well-ordered arrays that maintain protein biochemical activity. AFM force measurements may then be performed on these protein patches to induce and monitor conformational changes. This has been used previously to measure the free-energy difference between two stable conformations of Maltose Binding Protein. It is thus proposed that the concurrent application of FRET will allow for a more precise and detailed determination of a free-energy landscape for proteins immobilized via nanografting.